(untitled) (Research, Society and Development, 2020)
In view of the current oil crises, resulting from the increase in the prices of barrels, in addition to the possibility of depletion in the near future of this raw material, comes up need for a sustainable policy in relation to the sources of energy generation. In this sense, bioethanol generated from agro-industrial residues and fruits, appears as an alternative. Mango (Manguifera indica), in the Tommy Atkins variety, is the most produced and consumed in the country. This consumption and processing generates a large amount of organic waste. The mango peel is classified as a lignocellulosic raw material, with interesting amounts of cellulose and hemicellulose, essential factors for the production of bioethanol, a sustainable fuel. One of the ways to obtain this biofuel is through the acid hydrolysis of this raw material that provides fermentable sugars. However, there are factors that influence the acid hydrolysis process, providing or not a better performance in the formation of these sugars. Thus, this work aimed to analyze the potential of mango peel flour as a raw material for the production of bioethanol, carrying out the process of acid hydrolysis. As a way to achieve this goal, the influence of the particle size and the agitation applied to the particles of this material was evaluated. It was observed from the analysis, that the influence of the magnetic stirring favored a higher yield in relation to the formation of sugars, which are the basis for the production of bioethanol.